To compare efficacy and safety of direct oral anticoagulants in patients with concurrent atrial fibrillation and bioprosthetic heart valve repair or replacement: a systematic review and meta-analysis. (3rd October 2022) - Kaur, A; Dhaliwal, A; Khandait, H; Konje, S; Bhatia, K; Sohal, S; Turagam, M; Gwon, Y; Mamas, M; Dominguez, A; Bhatt, D; Velagapudi, P
Abstract: Background: Use of direct oral anticoagulants (DOACs) is contraindicated in patients with mechanical valves. However data on their use in patients with atrial fibrillation (AF) and bioprosthetic valves (BV) is still limited. Purpose: To assess the safety and efficacy of DOACs versus Vitamin K antagonist (VKA) in patients with AF after BV repair or replacement. Methods: We performed a comprehensive review of electronic databases (PubMed, Embase, Scopus, Cochrane) using MeSH terms and keywords for DOACs, AF and BVs from inception through December 2021. Randomized clinical trials (RCT) or observational studies that reported clinical outcomes comparing DOACs versus VKA in patients with AF and BVs were eligible for inclusion. Ten articles were reviewed for full text. Primary outcome was a composite of all cause stroke or systemic embolic event. Secondary outcomes included major bleeding and all-cause mortality. Subgroup analysis stratified by study design was performed. Pooled risk ratio (RR) and 95% confidence interval (CI) were calculated using Mantel-Haenszel method with DerSimonian-Laird estimator for tau2 for random effects model. Interstudy heterogeneity was assessed using the Higgins I 2 value. All statistical analysis was performed using RevMan 5.4.1 software. Results: Ten studies (5 RCTs, 5 observational studies) with a total of 5, 333 patients (DOACs n=2434; VKA n=2899) were included. Aortic, mitral and mixed BV repair or replacement were 74.2%, 25.6% and 0.02% respectively. The mean age was 72.6±11.9 years. The mean follow-up was 15.7±12.9 months. Type of DOACs included apixaban (n=553, 22.7%), rivaroxaban (n=893, 36.7%), dabigatran (n=151, 6.2%) and edoxaban (n=837, 34.4%). There was no significant difference in primary outcome of stroke or systemic embolic event (RR: 0.79; CI: 0.56–1.11; p>0.05; I 2 =12%) or secondary outcomes of major bleeding (RR: 0.84; CI: 0.64–1.11; p>0.05; I 2 =45%), and all-cause mortality (RR: 0.84; CI: 0.64–1.11; p>0.05; I 2 =29%) between DOACs compared with VKA. Conclusion: In patients with AF and BV, DOACs are non-inferior to VKA for risk of stroke or systemic embolism, major bleeding, and all-cause mortality. Thus, DOACs can serve as a viable alternative to VKAs which have a narrow therapeutic index, multiple drug interactions, and require frequent monitoring. Funding Acknowledgement: Type of funding sources: None.